Plasmid-mediated tetracycline resistance in Campylobacter jejuni: expression in Escherichia coli and identification of homology with streptococcal class M determinant. - Taylor, D E (1986)
Plasmid pUA466, a 45-kilobase transmissible tetracycline resistance plasmid from Campylobacter jejuni was mapped with AvaI, AvaII, BclI, HincII, PstI, XhoI, and XbaI. The resistance determinant was cloned and expressed in Escherichia coli and was homologous with a class M determinant from Streptococcus spp.